1981
DOI: 10.1002/pol.1981.170190305
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of dicumyl peroxide‐induced crosslinking of linear polyethylene

Abstract: SynopsisThe course of intermolecular reactions induced by peroxide decomposition in linear polyethylene has been determined and compared with similar reaction systems in which the substrate is a lowmolecular-weight alkane. Efficiency of intermolecular coupling is 40% for an alkane and 25-30% for the polymer system. Competing reactions, which reduce coupling efficiency, are mainly disproportionation of the initially formed radicals and to a minor extent further reactions involving the products from the peroxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 15 publications
2
36
0
Order By: Relevance
“…Unsaturation was observed in the 1 H spectrum of the residue, suggesting the participation of radicals that originated from dodecene (produced by the disproportionation of two dodecane radicals). Qualitatively, this result was similar to that observed by Hulse et al 15 …”
Section: Dodecanesupporting
confidence: 82%
See 1 more Smart Citation
“…Unsaturation was observed in the 1 H spectrum of the residue, suggesting the participation of radicals that originated from dodecene (produced by the disproportionation of two dodecane radicals). Qualitatively, this result was similar to that observed by Hulse et al 15 …”
Section: Dodecanesupporting
confidence: 82%
“…They found that ϳ50 -60% of the formed n-pentadecane radicals were involved in dimer formation, as observed by liquid chromatography. In a similar study, Hulse et al 15 used n-tetradecane to elucidate the crosslinking mechanism in the peroxide modification of PE. They found that ϳ44% of the formed n-tetradecane radicals were involved in dimer formation.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐linked polyethylene blends were prepared by curing with DCP . To this end, EOC, LDPE, and HDPE were blended in a twin‐screw micro‐extruder (DSM Research) at 160 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…In an effort directed to solve some of these questions, there have been studies in the past dealing with fractions of linear PE, substances consisting in low molecular weight analogues to polyethylene, and other model polymers. [4][5][6][17][18][19] In this paper, we present some of the latest results found in our work on irradiation and peroxide crosslinking of hydrogenated polybutadienes (HPB). These polymers, which can be considered ethylene-butene random copolymers, were obtained from the catalytic hydrogenation of monodisperse linear polybutadienes produced by anionic polymerization.…”
Section: Introductionmentioning
confidence: 98%